2005
DOI: 10.3386/w11578
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Government Spending on Consumption

Abstract: Recent evidence suggests that consumption rises in response to an increase in government spending.That finding cannot be easily reconciled with existing optimizing business cycle models. We extend the standard new Keynesian model to allow for the presence of rule-of-thumb consumers. We show how the interaction of the latter with sticky prices and deficit financing can account for the existing evidence on the effects of government spending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
593
7
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(657 citation statements)
references
References 17 publications
41
593
7
16
Order By: Relevance
“…They found that, consistent with a Keynesian view, output and consumption increase in response to a positive government spending shock. These results are in line with those obtained in Burnside et al (2004), Fatás and Mihov (2001) and Galí et al (2007), among others. In contrast with these results, another stream of the literature has found that fiscal policy may have non-Keynesian effects.…”
Section: Empirical Evidencesupporting
confidence: 93%
See 2 more Smart Citations
“…They found that, consistent with a Keynesian view, output and consumption increase in response to a positive government spending shock. These results are in line with those obtained in Burnside et al (2004), Fatás and Mihov (2001) and Galí et al (2007), among others. In contrast with these results, another stream of the literature has found that fiscal policy may have non-Keynesian effects.…”
Section: Empirical Evidencesupporting
confidence: 93%
“…The results in the previous subsection seem at odds with the widespread view that the presence of hand-to-mouth (RoT) consumers, with a marginal propensity to consume equal to 1, is essential to obtain high fiscal multipliers (Galí et al, 2007), as these consumers can be considered constrained by an extreme form of financial market (non) participation (i.e. a limiting case where m b = 0).…”
Section: Indebted Households Versus Rule Of Thumb Consumersmentioning
confidence: 91%
See 1 more Smart Citation
“…Galí, López-Salido, and Vallés (2006) implement "rule-of-thumb" consumers, whose consumption equals labor income. 3…”
Section: Among Others) Formentioning
confidence: 99%
“…For this, the departure from the Ricardian equivalence is necessary. There are two alternatives: Overlapping generation structure or rule of thumb (liquidity-constrained consumers) structure, developed by Gali et al (2007). We discard the last alternative from our analysis because the rule of thumb is an ad-hoc assumption.…”
Section: Introductionmentioning
confidence: 99%